Efforts to Form Character in Early Children through the Martial Arts of Taekwondo at Dojang SMAN 1 Bonjol - Tamsil, Hafid Abdul; Ismaniar, Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the phenomenon of the uniqueness of efforts to form the character of early childhood through Taekwondo which is useful and can increase the potential and shape the character of children for the better. character building for early childhood through taekwondo at Dojang SMAN 1 Bonjol. This study aims to reveal the method of character building for early childhood through learning martial arts taekwondo at Dojang SMAN 1 Bonjol. This research approach is descriptive qualitative. Sources of data in this study were trainers/sabeum, PAUD parents, and the person in charge of group taekwondoin. The technique used in data collection is by means of observation, interviews, and documentation. The analysis technique in this research is data reduction, data presentation, and conclusion drawing. The validity of the data was obtained by using triangulation of sources and theories. The results of the study reveal that efforts to form the character of early childhood through taekwondo aim to make taekwondoin have character, confidence, responsibility, discipline, and courage in taekwondo, and with tiered learning that is used can make children's characters become more disciplined and responsible, by a taekwondoin-level learning system with a higher level is in charge of each group and the trainer/sabeum monitors and provides direction if there are children who are not serious in training.